First two mitochondrial genomes for the order Filobasidiales reveal novel gene rearrangements and intron dynamics of Tremellomycetes - Qiang Li; Zhijie Bao; Ke Tang; Huiyu Feng; Wenying Tu; Lijiao Li; Yunlei Han; Mei Cao; Changsong Zhao (IMA Fungus)
Abstract In the present study, two mitogenomes from the Filobasidium genus were assembled and compared with other Tremellomycetes mitogenomes. The mitogenomes of F. wieringae and F. globisporum both comprised circular DNA molecules, with sizes of 27,861 bp and 71,783 bp, respectively. Comparative mitogenomic analysis revealed that the genetic contents, tRNAs, and codon usages of the two Filobasidium species differed greatly. The sizes of the two Filobasidium mitogenomes varied greatly with the introns being the main factor contributing to mitogenome expansion in F. globisporum. Positive selection was observed in several protein-coding genes (PCGs) in the Agaricomycotina, Pucciniomycotina, and Ustilaginomycotina species, including cob, cox2, nad2, and rps3 genes. Frequent intron loss/gain events were detected to have occurred during the evolution of the Tremellomycetes mitogenomes, and the mitogenomes of 17 species from Agaricomycotina, Pucciniomycotina, and Ustilaginomycotina have undergone large-scale gene rearrangements. Phylogenetic analyses based on Bayesian inference and the maximum likelihood methods using a combined mitochondrial gene set generated identical and well-supported phylogenetic trees, wherein Filobasidium species had close relationships with Trichosporonales species. This study, which is the first report on mitogenomes from the order Filobasidiales, provides a basis for understanding the genomics, evolution, and taxonomy of this important fungal group.